Os atingidos por barragens do rio Tocantins : perdas simbólicas e materiais dos afetados pela UHE peixe angical - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2019)
The Brazilian energy matrix stands out in a worldwide level due to the prepoderance ofrenewable sources, mainly by the generation ensured by the hydroelectric plants. Nevertheless, the implementation of those enterprises result in irreversible socio-environmental impacts, affecting mostly the traditional populations, reparian communities and small farmers, with the compulsory displacement from the areas where they live, near or on the banks of the rivers, where the hydroelectric plants are going to be built. This article analyses the process of material and symbolic losses endured by the families who are affected by the Peixe-Angical -UHE –Hydroelectrical Plant and transferred to the Piabanha I and Piabanha II settlements, located in the town of São Salvador do Tocantins, in the state of Tocantins, in the north region of Brazil. The data were obtained through interviews with the ones who were impacted, what made it possible to identify the difficulties on the maintenance of the subsistence; the breaking of affectional bonds, besides the variances on the relationship with nature environmentand the daily practices of the affected people.
The impacted by dams in the Tocantins river: symbolic and material losses of the affected people by the Peixe-Angical Hydroelectric Plant
Keywords: Hidrelétricas; UHE Peixe Angical; Perdas simbólicas; Reassentamentos; Atingidos por barragens; Estado do Tocantins; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA